Experimental dermatological surgery: An animal model for developing skills with dermal fillers - Juliana Catucci Boza; Vanessa Santos Cunha; Claudia Dickel de Andrade; Isabel Cristina Palma Kuhl (Wolters Kluwer Medknow Publications, 2011)
The importance of laboratory experiments in the formation of physicians is well recognized since they facilitate scientific development and enhance technical skills. Dermal filling procedures are performed for the correction of wrinkles, rhytids, scars, and lipodystrophy. Till date, experimental models for the training of dermal filling techniques have not been studied. To demonstrate an experimental laboratory model for the training of dermal filling techniques in an animal model. The heads of pigs were used for this purpose, together with Carbopol gel at different densities, which was used to simulate the fillers available in the market. Needles and specific cannulas were used to apply the fillers into the creases and other areas of the pig skin. The pig head appears to be a suitable model for this training. Carbopol gel is a good choice for simulating fillers. This model of laboratory experiment requires a minimum of infrastructure; it is a low-cost alternative and facilitates practical training in the application of dermal fillers.